Pengembangan Media Pembelajaran Sidara untuk Meningkatkan Hasil Belajar Murid di Kelas V MIS Al-Mourky - Gamar Abdullah; Kudus; Ade Mahniar (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study was motivated by Grade 5 students’ difficulties in understanding the science topic of the human circulatory system, which tends to be abstract when taught mainly through verbal explanation and textbooks. Therefore, a concrete learning medium is needed to help students visualize and comprehend the concepts. The study aimed to examine (1) the feasibility, (2) practicality, and (3) effectiveness of a concrete learning medium called Sidara (Circulatory System) for Grade 5 science learning at MIS Al Mourky. The research employed a Research and Development (R&D) design using the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate) and was conducted in the first semester of the 2025/2026 academic year. The trial participants were 17 Grade 5 students. Feasibility data were collected through expert validation (content expert and media expert), practicality data through teacher and student response questionnaires and implementation observation, and effectiveness data through a pretest–posttest achievement test analyzed using the N-Gain formula. The results showed that the Sidara medium achieved an average feasibility score of 91.25% (very feasible) and an average practicality score of 93.27% (very practical). Its effectiveness was indicated by an increase in the mean score from 55.65 (pretest) to 84.94 (posttest), with an N-Gain of 0.66 (moderate). In conclusion, the concrete Sidara learning medium is feasible, practical, and effective for improving students’ learning outcomes on the circulatory system topic.